Music Culture Teacher In Universal Education Schools (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article provides detailed information about the reforms in the field of music, culture, and art in the Republic of Uzbekistan, the activities of pedagogues, the opportunities given to teachers, and recommendations for improving the pedagogical skills of teachers.